Piloting a Cognitive-Behavioral Intervention for Family Members Living With Individuals With Severe Mental Disorders. (September 2014) - Polo-López, Rocío; Echeburúa, Enrique; Berry, Katherine; Salaberría, Karmele
Living with a person who experiences mental health problems can have an adverse effect on well-being. The aim of this study is to evaluate the effectiveness of a psychological treatment for relatives of people with mental health problems, byusing an interrupted time-series design. The sample comprised 20 individuals, who completed assessment measures at baseline and 6 months later. Sixteen of these participants then received the treatment and were assessed again at the end of the program. There were no significant changes in outcomes between the baseline and the second assessments done 6 months later and there were significant improvements in well-being following treatment The program shows promise as a treatment for relatives of people with mental health problems and therefore warrants further evaluation in more controlled studies.